The early market access vehicle – An innovative demand-driven model to catalyse introduction of new optimal health products in low- and middle-income countries - Ademola Osigbesan; Ikechukwu Amamilo; Aayush Solanki; Robert Matiru; James Conroy; Alya Omar; Karin Hatzold; Carolyn Amole; Kehinde Onasanya; Janet Ginnard (Health Policy Open)
Low-and middle-income countries (LMICs) account for a significant proportion of the burden of disease for communicable illnesses globally; with malaria, tuberculosis (TB), and HIV/AIDS being the leading causes of death. Despite this disparity, LMICs often have limited or delayed access to newer optimal health products compared to high-income countries (HICs). This limitation in access, driven by a myriad of barriers, undermines the potential health benefits that could be gained in LMICs through the introduction of better health products. To improve this inequity, governments in HICs, non-governmental organizations, and pharmaceutical companies, often resort to establishing donation programs for LMICs, to circumvent some of the access barriers. While well-implemented donation programs have the potential to improve access to new products, poorly executed donation programmes are common. These often have negative effects such as: overreliance on donations by recipient countries, dumping of short-dated or unwanted products, costs of waste disposal where unsuitable or excess products are received, and a lack of focus on access sustainability planning. Unitaid’s early market access vehicle (EMAV) is an innovative demand-driven access model for introducing new optimal health commodities in LMICs. An EMAV entails a conditional purchase commitment to the manufacturer for a defined quantity of selected products in exchange for a set of access commitments, required to facilitate equitable access in the target markets. EMAVs are designed to link catalytic donations to pathways for sustainable access. Unitaid, in collaboration with its partners, has leveraged the EMAV to introduce two innovative health products in a number of LMICs. This article discusses the EMAV model and builds the case on why stakeholders working on new product access should consider this approach as an alternative to traditional donation programmes.